Leadership styles, innovative work behaviour and employees’ innovativeness at Tenaga Nasional Berhad (TNB) Johor / Seri Mira Nazrina Nazip and Nur Nazirah Shahril - Nazip, Seri Mira Nazrina; Shahril, Nur Nazirah (Faculty of Business and Management, 2016)
This thesis will explain the result of leadership style that will give impact to employee innovativeness. There are four variables for this thesis. The first two independent variables are Transformational Leadership Style and Transactional Leadership Style. We are doing a research on mediating variable which is Innovative Work Behaviour (IWB) that will give impact on dependent variable. The dependent variable that will be tested is Employee Innovativeness (EI). The aim for this thesis is to measure whether transformational leadership will influence innovative work behaviour (IWB), or transactional leadership will influence more IWB among the employees. Other than that, is it true that if Innovative Work Behaviour will increase more the employee’s innovativeness than when there is no innovative work behaviour. This research is being conducted at Tenaga Nasional Berhad (TNB) Johor in Tenaga Nasional Berhad Department (TNBD). In completing this research, about 210 questionnaires have been distributed to respondents. For the first part at demographic section, we are going to investigate six types of respondent’s background and other three sections of questions for each variable. The Likert-type scale was adapted and tested to the respondents. In order to get a good result based on the questionnaires answered by the respondents, we are using SPSS program and Process Macro to analyse data from the information gathered. From the findings, it can be concluded that there is strong relationship between Innovative Work Behaviour (IWB) and Employees’ Innovativeness (EI). In addition, transformational leadership is the most leadership style being chosen by the respondents. Therefore, in summary the Innovative Work Behaviour (IWB) have the strongest effect towards Employees’ Innovativeness.